The Morris Intercultural Education Initiative: A Decade of Advancing Democracy Through Community-Engaged Learning in the Rural Midwest - Cristina Ortiz; Tammy Berberi; Thomas Genova; Windy G. Roberts (Journal of Community Engagement and Scholarship)
While ethnoracial diversity is associated with metropolitan areas in the popular imagination, Latinx people have been moving increasingly into rural spaces during this century. Rural communities often have less infrastructure to adapt to changing linguistic and intercultural circumstances than do their urban counterparts. Following a community needs and assets assessment, the Morris Intercultural Education Initiative (MIEI) was founded in 2013 as a collaboration between the University of Minnesota Morris Clifford J. Benson Center for Community Partnerships, the local Latinx population, and the area school district to address disparities in literacy and academic outcomes and to promote community integration in West Central Minnesota. MIEI currently administers four programs: Community English as a Second Language, the Teaching Reading and Empowering Children program, the Jane Addams Project for intercultural exchange, and the Tercero Community Interpreter Workshop Series. This retrospective article explores the genesis and organic responsiveness of MIEI programs through Freirean praxis and offers wisdom to those who wish to pursue similar projects in their own communities. Reflecting on their own problematic positionality as relatively privileged professional intellectuals in an intercultural rural environment, the authors argue that it is important to understand others in terms of the strengths and assets that they contribute to efforts to build culturally agile, democratic institutions.